Counseling and psychotherapy : a Christian perspective - Tan, Siang-Yang, 1954- (Grand Rapids, MI : Baker Academic, 2011)
This text combines cutting-edge expertise with deeply rooted Christian insights to offer a comprehensive survey of ten major counseling and psychotherapy approaches. For each approach, Siang-Yang Tan provides a substantial introduction, assessing the approach's effectiveness and the latest research findings or empirical evidence for it. He then critiques the approach from a Christian perspective. Tan also includes hypothetical transcripts of interventions for each major approach to help readers better understand the clinical work involved. The book also presents a Christian approach to counseling and psychotherapy that is Christ centered, biblically based, and Spirit filled. It will work well for marriage and family, social work, ministry, counseling, and psychology courses. Christian counselors and psychotherapists, pastors, chaplains, and lay counselors will also benefit from Tan's expertise -- Publisher description.
Basic issues in the practice of counseling and psychotherapy -- Overview of counseling and psychotherapy: theory, research, and practice -- The person of the counselor -- Legal and ethical issues in counseling and psychotherapy -- Major counseling and psychotherapy theories and techniques --
Includes bibliographical references and indexes.
Keywords: Counseling -- Religious aspects -- Christianity; Counseling; Psychotherapy -- Religious aspects -- Christianity; Psychotherapy